Improving the Assessment of Disaster Risks to Strengthen Financial Resilience : A Special Joint G20 Publication by the Government of Mexico and the World Bank - Government of Mexico; World Bank (World Bank, Washington, DC, 2017)
Rising losses from adverse natural events are compelling leaders of countries to develop more proactive approaches to risk management. In 2011 the world witnessed record losses from disasters caused by natural hazards with estimated costs of up to US$380 billion. Events in both developed and developing countries have shown that this is not a threat facing just one part of the world. In this context, the Mexican G20 Presidency included this growing threat to sustainable development on the group's agenda, a decision which was welcomed by G20 finance ministers and central bank governors. The economic costs of disasters complicate public financial management for many countries. Natural hazards are nondiscriminatory, potentially affecting all countries irrespective of economic status. The negative fiscal impacts of disasters can hamper longer-term growth and economic development. While lower income countries bear the brunt of the human impact from disasters, middle income countries experience the largest economic impact relative to GDP. Responding to a G20 mandate, this publication brings together the experiences of G20 countries in protecting their populations and assets against natural hazards. Prevention is better than cure; there is a need to raise awareness about disaster risks and their potential financial consequences. Increased resilience and sustainable development will require a more proactive approach to tackle risk at its roots. Preparedness measures to cope when disasters strike need to be combined with ex ante measures to avoid disasters in the first place. The need for better information on adverse natural events and associated economic, fiscal and social impacts emerges as a key message. Countries can strengthen their financial resilience to disasters. Governments should stimulate innovative financial solutions with and leverage the technical and financial capacity of the reinsurance and capital markets through public private partnerships.